A Review of Recent Bank Failures - Coyle, Eunice S. (The Review of Economics and Statistics, 1932)
THE MONTHLY RECORD NTIL November I930, the banks seemed to be weathering depression quite well. Though suspensions had increased somewhat in I929 even before the downturn of business and speculation, and thereafter increased more, yet as late as October I930 the record did not look bad against such earlier periods as the winter of I926 or I923-24; and the fact that suspensions during the spring and summer of I930 were exceptionally numerous for that time of year